Cerebellar Involvement in Clumsiness and Other Developmental Disorders - Richard B. Ivry (Neural Plasticity)
Cerebellar abnormalities have been linked to a number of developmental disorders. Much evidence is based on the analysis of highresolution MRI scans. Imaging and behavioral studies have led researchers to consider functional contributions of the cerebellum beyond that associated with motor control. I review this literature, providing an analysis of different ways to consider the relation between cerebellar abnormalities and developmental disorders. Interestingly, although clumsiness is a problem of coordination, the contribution of cerebellar dysfunction to this developmental problem has received little attention. Select studies indicate that some clumsy children have difficulties on tasks requiring precise timing, similar to that observed in adult patients with cerebellar lesions. I suggest that the underlying neural bases of clumsiness are heterogeneous, with cerebellar dysfunction likely a major contributor for a subpopulation of such children.